2021
DOI: 10.1007/s13365-020-00938-w
|View full text |Cite
|
Sign up to set email alerts
|

Detection of SARS-coronavirus-2 in the central nervous system of patients with severe acute respiratory syndrome and seizures

Abstract: This study was designed to evaluate whether severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) can directly target the central nervous system (CNS). We present four patients suffering from the loss of consciousness and seizure during the clinical course of COVID-19 infection. In addition to positive nasopharyngeal swab tests, SARS-CoV-2 has been detected in their cerebrospinal fluid. This report indicates the neuroinvasive potential of SARS-CoV-2, suggesting the ability of this virus to spread from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…• Neurodegeneration CSF biomarkers: The most frequently tested CSF neurodegeneration biomarkers were Tau protein, NfL and GFAP, in 33, 51 and 33 cases, respectively. Increased levels were found in 36%, 71% and 18%, respectively 9,61,66,70,77 . One study found a correlation between Tau and NfL levels and the opening CSF pressure 9 .…”
Section: Resultsmentioning
confidence: 96%
“…• Neurodegeneration CSF biomarkers: The most frequently tested CSF neurodegeneration biomarkers were Tau protein, NfL and GFAP, in 33, 51 and 33 cases, respectively. Increased levels were found in 36%, 71% and 18%, respectively 9,61,66,70,77 . One study found a correlation between Tau and NfL levels and the opening CSF pressure 9 .…”
Section: Resultsmentioning
confidence: 96%
“…Patient autopsies have revealed neuronal loss[ 75 ], often associated with an immune response against the virus in the CSF. Few reports showed that patients who tested positive for SARS-CoV-2 in their CSF but did not have any significant risk factors or a history of neurological diseases manifested neurological symptoms, such as seizures and loss of consciousness[ 76 ].…”
Section: Neuroinvasion By Sars-cov-2mentioning
confidence: 99%
“…Several disorders, such as hematologic diseases, cardiovascular abnormalities, and infection increase the risk of IS (Woldu 2020 ; Ferro and Infante 2021 ; Virani et al 2021 ). Coronavirus disease 2019 (COVID-19) results from SARS-CoV-2 is an inflammatory disorder (Leisman et al 2020 ; Gorji and Khaleghi Ghadiri 2021 ), which can affect the central nervous system (CNS) (Soltani Zangbar et al 2021 ; Rezaeitalab et al 2021 ). COVID-19 predisposes some patients to a wide range of neurological complications, including stroke (Ntaios et al 2020 ).…”
Section: Introductionmentioning
confidence: 99%